Numerical solutions of boundary value problems of non-linear differential equations - Chowdhury, Sujaul; Faruque, Syed Badiuzzaman; Das, Ponkog Kumar (Boca Raton : Taylor and Francis, 2022)
"Numerical Solutions of Boundary Value Problems of Non-linear Differential Equations presents in comprehensive detail numerical solution to boundary value problems of a number of non-linear differential equations. Numerical solutions have been presented in comprehensive detail Newton's iterative method has been applied to solve system of non-linear algebraic equations encountered In each case, Euler solutions have been obtained to serve as a cross-check as to any mistakes Mathematica has been used as the program. Programs written in Mathematica have been presented for re-use This book is primarily aimed at final year undergraduate students of Physics and Mathematics who have undertaken a course on computational physics"--
Includes bibliographical references and index.
Mathematics
English
Description based on print version record and CIP data provided by publisher.
Keywords: Boundary value problems -- Numerical solutions; Nonlinear boundary value problems -- Numerical solutions